AtNOT1 Is a Novel Regulator of Gene Expression during Pollen Development. (28th October 2019) - Motomura, Kazuki; Arae, Toshihiro; Araki-Uramoto, Haruka; Suzuki, Yuya; Takeuchi, Hidenori; Suzuki, Takamasa; Ichihashi, Yasunori; Shibata, Arisa; Shirasu, Ken; Takeda, Atsushi; Higashiyama, Tetsuya; Chiba, Yukako
Abstract: Development of pollen, the male gametophyte of flowering plants, is tightly controlled by dynamic changes in gene expression. Recent research to clarify the molecular aspects of pollen development has revealed the involvement of several transcription factors in the induction of gene expression. However, limited information is available about the factors involved in the negative regulation of gene expression to eliminate unnecessary transcripts during pollen development. In this study, we revealed that AtNOT1 is an essential protein for proper pollen development and germination capacity. AtNOT1 is a scaffold protein of the AtCCR4–NOT complex, which includes multiple components related to mRNA turnover control in Arabidopsis. Phenotypic analysis using atnot1 heterozygote mutant pollen showed that the mature mutant pollen failed to germinate and also revealed abnormal localization of nuclei and a specific protein at the tricellular pollen stage. Furthermore, transcriptome analysis of atnot1 heterozygote mutant pollen showed that the downregulation of a large number of transcripts, along with the upregulation of specific transcripts required for pollen tube germination by AtNOT1 during late microgametogenesis, is important for proper pollen development and germination. Overall, our findings provide new insights into the negative regulation of gene expression during pollen development, by showing the severely defective phonotype of atnot1 heterozygote mutant pollen.